State Plan Proposals 1988-89 Volume I Government of West Bengal - Planning Commission (Planning Commission, 1987)
The introductory chapter deals with an over view of the economy in the context of the prevailing socio-economic situation of the State as also of the performance during the preceding two years of the 7th Plan, the compulsion of the economy leading to the proposed size in the 4th year (1988-89) and the resource back-up to match the physical plan.
Government of West Bengal, Development and Planning Department